Theoretical Studies of Molecular Structure and Vibrational Spectra of Melaminium Salt: 2,4,6-Triamino-1,3,5-triazin-1,3-ium Tartrate Monohydrate - ESMER, KADİR (SPRINGER HEIDELBERG, 2012)
The optimized geometric parameters and vibrational frequencies of melaminium salt: 2,4,6-triamino-1,3,5-triazin-1,3-ium tartrate monohydrate in the ground state have been calculated by using the Hartree-Fock (HF) and density functional method (B3LYP) with 6-31G(d) and 6-31++G(d,p) basis sets. The results of the optimized molecular structure are presented and compared with the experimental X-ray diffraction. The molecule contains the weak hydrogen bonds of N-H. . .O and O-H. . .O types. The computed vibrational frequencies were used to determine the types of molecular motions associated with each of the experimental bands observed. The percentage weightage of internal coordinates contribution to the frequencies are given.
Keywords: Melaminium salt; 2,4,6-Triamino-1,3,5-triazin-1,3-ium tartrate monohydrate; Hydrogen bond; DFT; HF; IR spectra; DENSITY-FUNCTIONAL THEORY; NONLINEAR-OPTICAL PROPERTIES; HARTREE-FOCK; CRYSTAL-STRUCTURE; ORBITAL METHODS; BASIS-SETS; CONFIGURATION; ARCHITECTURE; DERIVATIVES; DIHYDRATE